Islamization of Human Knowledge: An Analysis of Methodo-logical Issues Pengislaman Ilmu Manusia: Satu Analisis Isu-Isu Metodologi - Mumtaz Ali, Muhammed (Journal of Islam in Asia (E-ISSN 2289-8077), 2014)
Abstract The concept of Islamization of Human Knowledge (IOHK) is generally understood as the movement of epistemological and methodological change. But the issue of the methodology of Islamization of Human Knowledge is either confined to the issue of Islamization itself or misunderstood as a whole. In fact, the issue of methodology is that of Islamic thought. Ismail Raji al Faruqi and Abdul Hamid Abu Sulayman discussed this issue of methodology as that of Islamic thought and identified some specific steps for dealing the Islamization of Human Sciences. This paper is devoted to identifying and analyzing the views of scholars who consider Islamization of Human Knowledge as methodological issue. Keywords: Islamization, Human Knowledge, Methodological Issue, Epistemology, Analysis. ****************************** Abstrak Konsep pengislaman ilmu manusia secara amnya difahami sebagai pengerakan bagi perubahan epistemologi dan metodologi. Tetapi isu metodologi pengislaman ilmu manusia sama ada terhad kepada isu pengislaman sendiri atau disalah faham secara keseluruhannya. Hakikatnya, isu metodologi ialah pemikiran Islam. Ismail Raji al Faruqi dan Abdul Hamid Abu Sulayman membincang mengenai isu metodologi sebagai pemikiran Islam dan mengenal pasti beberapa langkah tertentu untuk menangani Pengislaman Sains Kemanusiaan. Karya ini ditumpukan untuk mengenal pasti dan menganalisis pandangan ulama yang menganggap pengislaman ilmu manusia sebagai isu metodologi. Kata Kunci: Pengislaman, Ilmu Manusia, Isu Metodologi, Epistemologi, Analisis .